Study of the strength and erosive behavior of CaCO3/glass fiber reinforced polyester composite (eXPRESS Polymer Letters)
In this study, the strength and erosive characteristics of CaCO3 filled unsaturated polyester/glass fiber (UPR/GFR) composite are evaluated. Samples of UPR with 40, 50 and 60 wt% content of CaCO3 and different CaCO3 particle sizes of 1, 2, 3, 5 and 10 micron were prepared and tested under tensile loading, indentation and erosion conditions. The tensile strength, hardness and erosion wear rate of unsaturated polyester/glass fiber (UPR composite)/CaCO3 composite were obtained and evaluated. The results showed that the higher is the percentage of CaCO3 in the composite and the smaller is the CaCO3 particle size, the higher is the strength and the erosive resistance of the glass fiber reinforced/unsaturated polyester composite (UPR-GFR). Furthermore, the highest erosion wear rate is at 90° impingement angle. Finally the results show that the erosive wear of CaCO3 content UPR/GFR composite in a brittle manner.